Does acute vibration exercise enhance horizontal jump performance? - Cochrane, D. J.; Booker, H. (Journal of Sports Science & Medicine, 2014)
The aim of this study was to investigate the acute effect of vibration exercise (VbX) on repetitive horizontal jumping performance and to examine the duration of the rest interval between the horizontal jump sets following acute VbX. Fourteen track athlete males (age 20.8 ± 1.8 yr; height 1.80 ± 0.05 m; body mass 73.1 ± 7.5 kg) performed four conditions in a randomised order; (a) VbX with 1 min rest between repetitive horizontal jump (RHJ) sets [VbX-1min]; (b) VbX with 2 min rest between RHJ sets [VbX-2min]; (c) No VbX with 1 min rest between RHJ sets [Con-1min]; (d) No VbX with 2 min rest between RHJ sets [Con-2min]. Intermittent VbX (six 60 s exposures with 30 s rest) at 26 Hz (6 mm peak-to-peak displacement) was performed in an isometric squat position (120° of knee flexion). The mean values of distance, velocity and time taken of RHJ from the four conditions were used in repeated measures [condition (VbX and Control) and rest period (1min; and 2min)] ANOVA. There was a condition effect such that VbX significantly increased RHJ distance (p < 0.05) compared to control (no VbX). Furthermore, VbX significantly increased RHJ velocity (p < 0.05) compared to no VbX and there was an interaction effect (condition x rest) where the velocity was significantly higher in VbX-2min compared to VbX-1 min, Con-2min, and Con-1min respectively. Acute intermittent VbX has the ability to enhance repetitive horizontal jump distance and velocity, which could be used as an additional method for warm-up intervention to increase explosive power performance.